Mieszanie krwi - Śnieżko, Dariusz (My University, 2013)
The article discusses Jewish conversions to Catholicism in Poland before 1795, presenting the issue from the perspective of discourses of anthropology, religion, and, importantly, class stratification, with reference to the most important European contexts. The survey of source texts includes selected authors, such as Wacław Potocki or Walerian Nekanda Trepka, allowing for an introductory sketch of relations between the idea of nobility, anti-Judaism, and antisemitism.
Blood Mixing
Keywords: Jew; nobility; conversion; knighting; anti-Judaism; antisemitism